PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BURGER KING PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MERCU BUANA (Studi pada Mahasiswa Mercu Buana Fakultas Ekonomi dan Bisnis) - Muhammad Mulqi Azmar (Universitas Mercu Buana, 2025)
This research aims to analyze brand image, product quality and price on Burger King purchasing decisions among students at the Faculty of Economics, Mercu Buana University. This research uses a causality research design with a quantitative approach. The population in this study were students at the Faculty of Economics, Mercu Buana University. The sampling technique used in this research is purposive sampling technique and the number of consumers sampled in this research is 180 respondents. The data collection method uses a survey, with a questionnaire research instrument. The data analysis method uses Partial Least Square (Smart-PLS) version 4.0. Based on data analysis, this research can be concluded that brand image has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions and price has a positive and significant effect on purchasing decisions. buying decision